The Impact of Store Atmosphere on Customer Loyalty: The Mediating Roles of Customer Satisfaction and Purchase Intention in The Coffee Retail Industry - Jofani Augustine Wijaya; Devin Lucius; Bambang Suwarno (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The rapid growth of the retail coffee industry in Indonesia has intensified competition, requiring firms to understand the determinants of customer loyalty beyond physical store design. This study aims to examine the effect of store atmosphere on customer loyalty, with customer satisfaction and purchase intention as mediating variables, in a drive-thru coffee retail context in Medan. The population comprised all customers who made purchases at the Kopi Kenangan Gatot Subroto outlet in Medan, and data were gathered utilizing a non-probability purposive sampling method. A total of 389 valid responses were obtained from customers who had made at least one purchase and were willing to complete the questionnaire. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that customer satisfaction has a strong and significant direct effect on customer loyalty (β = 0.746, p < 0.001), and purchase intention indirectly influences loyalty through satisfaction. However, store atmosphere does not significantly affect satisfaction, purchase intention, or loyalty. The model explains 56.2% of the variance in customer loyalty, indicating moderate predictive power. These findings emphasize that post-consumption evaluation and experiential satisfaction play a more critical role than atmospheric cues in building loyalty in the modern coffee retail industry.